Till Circumstances Do Us Part: A Socio-Ethical Analysis of Divorce among Christians in Nigeria (Global Journal of Human-Social Science, 2019)
The rate of divorce among Christian couples in the 21st Century has reached an alarming proportion with attendant negative effects on the church and the society. Given this, much has been done to address the trend, but obviously success has been minimal. Also, researches abound on the subject matter in various fields of study. This paper discussed the incidence of divorce as a recurring problem among Christians in Nigeria, with reference to its social and ethical implications. It interrogated contemporary justification for divorce, as against biblical injunctions, and recommended ways of stemming its tide in order to have a church and society that are free from the clutch of broken homes resulting in juvenile delinquency and other social vices. Data were garnered through oral interviews with some clerics, married couples and identified divorcees. A content analysis of relevant academic materials was also done to complement the primary data.
Keywords: divorce; christian marriages; nigeria; socioethical implications